How to minimize the circulatory arrest time by using the Thoraflex Hybrid prosthesis: the 'release and perfuse' technique. (12th August 2021) - Piperata, Antonio; d'Ostrevy, Nicola; Busuttil, Olivier; Pernot, Mathieu
Abstract: Although the frozen elephant trunk technique permits a complete single-stage treatment in patients with extended thoracic aortic disease, the problem of circulatory arrest time remains unsolved. We propose a simplified use of the Thoraflex Hybrid prosthesis to minimize the circulatory arrest time. Abstract : Despite all the advantages of the frozen elephant trunk (FET) procedure, the problem of circulatory arrest time remains unsolved.